Evolução da rede de drenagem na Bacia do Alto Rio Paraguaçú: capturas fluviais, drenagem transversa e pirataria de bacias - Claudia Mendes Cordeiro (2019)
The Chapada Diamantina region marks the boundary between the hydrographic basins of the Paraguaçú and São Francisco rivers and constitutes one of Brazil’s most geomorphological landscapes. However, the Neogene/Quaternary evolution of its drainage network has never been investigated. An analysis of the drainage organization of the Upper Paraguaçu Basin, a geographic region that largely coincides with the eastern Chapada Diamantina compartment, reveals evidence of drainage rearrangement processes, primarily elbows of capture, proto-captures, and oversized valleys in coincident sites with transverse drainage network gaps and at high-altitude altimetric points located in the Serra do Sincorá mountain range. The purpose of this research was to investigate the occurrence and role of drainage rearrangement processes in the Chapada Diamantina morphogenesis and understand how these processes interact in the formation of transverse drainage networks, especially in the organization of the local and regional drainage system. Our discussion was based on the hypothesis that the Chapada Diamantina drainage network was reconfigured by drainage rearrangement processes, namely, river captures. The methodological procedures used in the research were: (a) fieldwork to verify the morphological evidence of rearrangement and characterization of the relief; (b) cartographic analyses, geoprocessing, and remote sensing through which it was possible to generate thematic maps and integrated analyses, and Digital Elevation Models (MDE Alos Palsar 12.5 meters with resampled resolution and SRTM 30 meters), which allowed the preparation of (c) morphometric index parameters, such as the Hack Index (1973), Relief Dissection, Drainage Density, and the Convexity Index. A model was designed in 3D and 2D to synthesize a proposed evolution of the drainage network in the Upper Paraguaçú River Basin and its influence on adjacent basins. The results indicate the existence of three large Neogene/Quaternary river captures where areas formerly belonging to the São Francisco river basin were pirated to the Paraguaçu River: (i) The Santo Antônio River capture (Pai Inácio Capture); (ii) the Irecê Basin capture – Rio Santo Antônio (Karst Piracy), and (iii) the current Paraguaçú River capture (Mucugê Capture). Finally, the results also show that this set of river catches resulted in an energy input into the river system of the eastern region of Chapada Diamantina, Bahia (Serra do Sincorá), which has dissected the this compartment’s relief, mainly in the Irecê Basin and pediplain. This must have altered the flow of the rivers to the point of pirating a significant drainage area that had previously been discharged into the São Francisco Basin and began to flow into the Paraguaçú Basin (the Brazilian East Basin), thus altering the regional morphogenesis, which would confirm our initial hypothesis.